The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1956
DOI: 10.1021/ja01590a025
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolism in Bakers' Yeast.1,2 I. Time Course Study of Glucose Utilization

Abstract: The time course study of the utilization of specifically labeled glucose by yeast has been carried out under proliferating conditions. The rate of change of specific activity in the respiratory COs from the respectively labeled substrate agrees with the known breakdown pathways of glucose in this organism. Calculations were made on the basis of cumulative radiochemical recoveries of metabolic CO, from each labeled glucose which revealed that approximately 87% of the administered glucose was metabolized by way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1958
1958
1984
1984

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Acetate formed in this manner is presumably metabolized by way of the TCA process (10, 4), as also supported by the finding that the cumulative recovery of C-2 of glucose (equivalent to acetate carboxyl in the EMP-TCA scheme) in the respiratory CO2 (insert in fig 1) is considerably higher than that of C-6 of glucose (equivalent to acetate methyl) and eventually results in an overall ratio of 2 to 1 for CO2 from C-2 versus CO2 from C-6 of glucose. Similar findings have been reported in studies with proliferating yeast in which the TCA process is considered to be responsible for both respiration and biosynthesis of various carbon skeletons (9). The preferential utilization of acetate methyl carbon (hence C-6 or C-1 of glucose) in biosynthesis is thought to account for the observed ratio of C6/C2 of glucose in CO2.…”
Section: Fate Of the Labeled Glucose In Fruit: In Ordersupporting
confidence: 85%
See 1 more Smart Citation
“…Acetate formed in this manner is presumably metabolized by way of the TCA process (10, 4), as also supported by the finding that the cumulative recovery of C-2 of glucose (equivalent to acetate carboxyl in the EMP-TCA scheme) in the respiratory CO2 (insert in fig 1) is considerably higher than that of C-6 of glucose (equivalent to acetate methyl) and eventually results in an overall ratio of 2 to 1 for CO2 from C-2 versus CO2 from C-6 of glucose. Similar findings have been reported in studies with proliferating yeast in which the TCA process is considered to be responsible for both respiration and biosynthesis of various carbon skeletons (9). The preferential utilization of acetate methyl carbon (hence C-6 or C-1 of glucose) in biosynthesis is thought to account for the observed ratio of C6/C2 of glucose in CO2.…”
Section: Fate Of the Labeled Glucose In Fruit: In Ordersupporting
confidence: 85%
“…The characteristic ability of the succulents to incorporate a large net amount of CO2 in the form of organic acids has been recognized for a long time (9). Although the biochemical mechanisms of this phenomenon have received a great deal of attention, the physiological role has not been fully understood.…”
Section: Fate Of the Labeled Glucose In Fruit: In Ordermentioning
confidence: 99%
“…Using the radiorespirometric method (Wang et al, 1956), we made an estimate of the pathways GOLDMAN 1. Relation between the percentage of glucose oxidized by the hexose monophosphate pathway or the percentage of glucose-6-CI4 oxidized to C02, a measure of the terminal respiratory pathway, and the stage of development of resting Bacillus cereus terminalis suspensions.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in respiration quotient with increasing growth rate also implies that the catabolism of maltose and lactate to CO, is less efficient at higher than at lower growth rates. Liener & Buchanan (1951) reported that S. cerevisiae is able to satisfy up to 5 % of its carbon requirements by C 0 2 assimilation, and Wang et al (1956) proposed that up to 10 % of the pyruvate originating from glucose was involved in CO, fixation. It could well be that as the growth rate increased the importance of COz fixation reactions increased.…”
Section: Discussionmentioning
confidence: 99%